2011
DOI: 10.2147/jpr.s26476
|View full text |Cite
|
Sign up to set email alerts
|

Preincisional administration of intravenous or subcutaneous infiltration of low-dose ketamine suppresses postoperative pain after appendectomy

Abstract: BackgroundKetamine, an N-methyl-D-aspartate receptor antagonist, can suppress hyperalgesia and allodynia. The purpose of the present study was to evaluate the clinical efficacy of preincisional intravenous or subcutaneous infiltration of ketamine for postoperative pain relief after appendectomy.MethodsNinety patients, aged 18–60 years, scheduled for appendectomy was enrolled in this study. Patients were divided into three groups of 30 each and received subcutaneous infiltration of ketamine 0.5 mg/kg (KS), intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Preincisional IV administration of low-dose ketamine provides analgesia for 24 hours after surgery without significant side effects in patients undergoing appendectomy, whereas SC ketamine at the same dose only controls analgesia within the first 6 hours after surgery. 57 …”
Section: Resultsmentioning
confidence: 99%
“…Preincisional IV administration of low-dose ketamine provides analgesia for 24 hours after surgery without significant side effects in patients undergoing appendectomy, whereas SC ketamine at the same dose only controls analgesia within the first 6 hours after surgery. 57 …”
Section: Resultsmentioning
confidence: 99%
“…From the results obtained, we concluded that XaraColl implanted intraoperatively was able to target and control visceral pain more efficiently than continuous perfusion of the surgical wound with bupivacaine for 72 hours postoperatively 10. Hence, XaraColl may be of particular benefit for reducing the postoperative pain normally experienced by patients undergoing laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 93%
“…We have recently reported on the safety and efficacy of XaraColl, a bupivacaine-collagen implant, for postoperative analgesia in patients undergoing open inguinal hernioplasty9 and open gynecological surgery 10. From the results obtained, we concluded that XaraColl implanted intraoperatively was able to target and control visceral pain more efficiently than continuous perfusion of the surgical wound with bupivacaine for 72 hours postoperatively 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous trials, preincision tramadol and ketamine injections were separately examined, but in this clinical trial, we used a low dosage combination of both (21, 22). …”
Section: Discussionmentioning
confidence: 99%